Estimating Occupation and Location Specific Wages over the Life Cycle - Ilin, Elias; Terry, Ellyn (Business and Economic Research, 2022)
<span style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">In this paper we develop a novel method to project location specific life cycle wages for all occupations listed in the Bureau of Labor Statistics Occupational Outlook Handbook. Our method builds on the commonly used Mincer equation and improves it by providing a more nuanced relationship between years of experience and wages while also incorporating occupation and location specific factors. Our method consists of two steps. In the first step, we use individual level data from the Current Population Survey (CPS) to estimate the average number of years of experience associated with each percentile of the wage distribution. In the second step, we map this estimated average years of experience to the wage level percentiles reported in the Occupational Employment and Wage Statistics (OEWS) data for each occupation and area. Finally, we develop a model capable of projecting the trajectory of wages across all possible years of experience for each occupation in the OEWS data.